Características hidrogeomorfológicas das bacias hidrográficas dos Rios Santa Maria do Rio Doce e Santa Joana/ES - Mendonça, Patrícia Ramaldes (2013)
Sediment generated by erosion in watersheds often are carried by rain to water bodies compromising water quality. The objective of this study was to perform a comparative assessment of the watersheds Santa Maria do Rio Doce and Santa Joana about the potential generation of sediment from hydrogeomorfophology analysis, hydrossedimentology analysis and mapping of erosion fragility on the watersheds. Characterization of watersheds identified existing environmental scenarios, emphasizing the main aspects that affect erosion processes, such as terrain slope, soil type, use and land cover, among others. Hydrogeomorphology analysis was performed from the morphometric drainage basin data of linear, areal and hypisographic parameters. it was also attempted to relate the results of hydrossedimentology with hydrogeomorfology analysis. The mapping of erosion fragility contributed to the spatial understanding of the main focus of erosion in river basins. Thus, sub-basins were suggested interventions for erosion control and hydrosedimentological monitoring. The weighted average of erosion fragility classes allowed a more direct comparison with the values obtained for other parameters analised. Results related with morphometric parameters and weighted average of erosion fragility classes suggest that the tendency of sediment yield per unit area of Santa Maria do Rio Doce river basin is slightly higher than the corresponding to the Santa Joana basin. Hydrosedimentological data, although limited to a few rain events, allowed a sense of solid transport in the river of the two main basins. Analysis methods used in the study proved to be important tools for understanding the erosive dynamics on watersheds and, therefore, important tools for future projects to improve the water quality of the studied watercourses.